1991
DOI: 10.1111/j.1476-5381.1991.tb12478.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor subtypes coupled to generation of different second messengers in isolated tracheal smooth muscle cells

Abstract: 1 Activation of muscarinic receptor subtypes leads to contraction, an increase in the accumulation of inositol phosphates (IPs) and a decrease in adenosine 3': 5'-cyclic monophosphate (cyclic AMP) synthesis in tracheal smooth muscle. The concentrations of carbachol that produced a half-maximal effect (EC50) in inhibition of cyclic AMP generation, stimulation of IPs formation and contraction were 15 nM, 2.0M and 0.17 pM, respectively. 2 Pirenzepine, a selective M1 antagonist, displayed a low affinity for antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 25 publications
8
40
1
Order By: Relevance
“…The M2 type binding sites represent the major population (75 -90%) of muscarinic receptors (Roffel et al, 1988;Fryer et al, 1990;Lucchesi et al, 1990;Schaefer et al, 1992;Fernandes et al, 1992;Mahesh et al, 1992), except in guinea-pig trachea where both populations are approximately equal (Haddad et al, 1991). Among these receptor subtypes, muscarinic M3 receptors are unanimously found to mediate contraction under normal conditions in vitro (Mutschler et al, 1988;Roffel et al, 1988;1990a;Yang et al, 1991;Gardier et al, 1991;Mahesh et al, 1992), presumably via activation of phospholipase C 1 Author for correspondence. (Roffel et al, 1990b;Yang et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The M2 type binding sites represent the major population (75 -90%) of muscarinic receptors (Roffel et al, 1988;Fryer et al, 1990;Lucchesi et al, 1990;Schaefer et al, 1992;Fernandes et al, 1992;Mahesh et al, 1992), except in guinea-pig trachea where both populations are approximately equal (Haddad et al, 1991). Among these receptor subtypes, muscarinic M3 receptors are unanimously found to mediate contraction under normal conditions in vitro (Mutschler et al, 1988;Roffel et al, 1988;1990a;Yang et al, 1991;Gardier et al, 1991;Mahesh et al, 1992), presumably via activation of phospholipase C 1 Author for correspondence. (Roffel et al, 1990b;Yang et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Among these receptor subtypes, muscarinic M3 receptors are unanimously found to mediate contraction under normal conditions in vitro (Mutschler et al, 1988;Roffel et al, 1988;1990a;Yang et al, 1991;Gardier et al, 1991;Mahesh et al, 1992), presumably via activation of phospholipase C 1 Author for correspondence. (Roffel et al, 1990b;Yang et al, 1991). The M2 receptors have been shown to inhibit fl-agonist-or forskolin-stimulated cyclic AMP production in intact canine, bovine and human airways smooth muscle cells (Sankary et al, 1988;Yang et al, 1991;Schaefer et al, 1992;Challiss et al, 1993;Widdop et al, 1993), as well as in membrane preparations of canine, bovine and guinea-pig trachealis (Jones et al, 1987;Meurs et al, 1992;Pyne et al, 1992), the latter demonstrating a direct inhibitory effect on adenylyl cyclase, presumably via the inhibitory Gprotein, Gi (Sankary et al, 1988;Pyne et al, 1992;Widdop et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of adenylate cyclase seems to be coupled to the M2 subtype and is distinct from the M3 subtype coupled to phospholipase C activation. The M3 muscarinic receptor is shown to mediate contraction of airway smooth muscle (Roffel et al, 1990;Yang et al, 1991), but a functional role of the M2 subtype in this tissue remains unclear. Fernandes et al (1992) suggested that stimulation of M2 muscarinic receptors in canine airway smooth muscle may play an important role in functional antagonism by decreasing the relaxation caused by agents such as isoprenaline and forskolin.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of competitive binding curves for pirenzepine yields a model of one binding site with low affinity (Hulme et al, 1990), indicating the absence of Ml muscarinic receptors in TSMC. The pKB value of pirenzepine for inhibition of generation of inositol phosphates inhibition of contraction and reversal of cyclic AMP attenuation (7.0, 7.1 and 6.7, respectively) were of low affinity (Hulme et al, 1990;Yang et al, 1991 (Brown & Brown, 1984;Candell et al, 1990;Yang et al, 1991). We found that methoctramine (a selective M2 antagonist) possessed a high affinity to antagonize cyclic AMP inhibition (pkB = 7.4), whereas it antagonized inositol phosphate formation (pKB = 6.0) and tracheal smooth muscle contraction (pKB = 6.1) with low affinity.…”
Section: Discussionmentioning
confidence: 99%